Restoration of CB1 receptor function in hippocampal GABAergic neurons rescues memory deficits in Huntington’s disease models - Di Franco, Nadia; Bengoetxea de Tena, Iker; Sanchez-Ruiz, Andrea; Pereda-Velarde, Alba; Enfedaque, Ferran; Gónzalez-Arias, Candela; Rio, Lluis Maria Miquel; Bortolozzi, Analia; Rodriguez-Puertas, Rafael; Costas-Insua, Carlos; Molina-Porcel, Laura; Vazquez-Oliver, Anna; et al. (Translational neurodegeneration, 2025)
Dysregulation of the endocannabinoid system (eCBS) and the loss of CB1 receptors (CB1R) in the basal ganglia are well-established hallmarks of Huntington’s disease (HD). As a result, significant research efforts have focused on targeting the eCBS to alleviate motor disturbances associated with the disease. Beyond its role in motor control, the eCBS is a complex signaling network critically involved in regulating learning and memory. Despite this, the potential involvement of eCBS dysfunction in the cognitive decline characteristic of HD, often manifested well before motor dysfunction, has remained largely unexplored.